Interphase effect on the effective magneto-electro-elastic properties for three-phase fib er-reinforce d composites by a semi-analytical approach - Espinosa Almeyda, Yoanh; Camacho Montes, Hector; Otero, José Antonio; Rodríguez Ramos, Reinaldo; Lopez Realpozo, Juan Carlos; Guinovart Diaz, Raul; Sabina, Federico J (2020)
A semi-analytical approach is proposed to determine the effective magneto-electro-elastic moduli of a fiber-reinforced composite. We especially focus on predicting the effective properties of three-phase periodic composite reinforced with unidirectional, infinitely long and concentric cylindrical fibers with square transversal distribution. The semi-analytical method is developed combining asymptotic homogenization and finite element meth- ods. Asymptotic homogenization method allows the statements of local problems that are solved by finite element method and the associated effective coefficients. Finite element method is implemented via the principle of minimum potential energy. The effect of inter- phase thickness and the fiber material properties on effective moduli is analyzed. Numer- ical computations were performed, and an exact agreement is obtained by comparing the semi-analytical approach with asymptotic homogenization method linked to the theory of potential functions of a complex variable.